2015
DOI: 10.2215/cjn.09660914
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Ig Free Light Chains with Mortality and ESRD among Patients with Nondialysis-Dependent CKD

Abstract: Background and objectives High levels of serum polyclonal combined Ig free light chains are associated with inflammation and decreased excretory kidney function, and they are an independent risk factor for mortality. Whether combined Ig free light chain predicted mortality and progression to ESRD in a stages 3-5 CKD cohort was assessed.Design, setting, participants, & measurements This was a prospective cohort study of 872 patients with stages 3-5 CKD (nondialysis) recruited into the Chronic Renal Insufficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…[14][15][16] Although we had only 17 (0.4%) participants with CKD category G1 in the meta-analysis, the results indicate that sFLC may have a role in all stages of pre-dialysis CKD. This is consistent with general population studies identifying an association between elevated sFLC and mortality in individuals without CKD.…”
Section: Mortalitymentioning
confidence: 84%
See 3 more Smart Citations
“…[14][15][16] Although we had only 17 (0.4%) participants with CKD category G1 in the meta-analysis, the results indicate that sFLC may have a role in all stages of pre-dialysis CKD. This is consistent with general population studies identifying an association between elevated sFLC and mortality in individuals without CKD.…”
Section: Mortalitymentioning
confidence: 84%
“…29 Second, in the studies included in this meta-analysis, the correlation between eGFR and sFLC (where reported) is moderate (r values of -0.56 and -0.49). 15,16 This indicates that whilst sFLC is in part associated with eGFR, a substantial contribution to differences in sFLC levels is independent of kidney function. For example, FLC undergo significant non-renal clearance through the reticulo-endothelial system, which accounts for a greater portion of clearance in CKD as kidney function declines.…”
Section: -28mentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies in CKD patients have demonstrated that high FLC levels are independently associated with overall mortality risk across different stages of CKD [40,41] . Not all studies were able to demonstrate this association though [42] .…”
Section: Free Light Chainsmentioning
confidence: 99%